PENGARUH LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X TGB PADA MATA PELAJARAN GAMBAR TEKNIK MANUAL JURUSAN TEKNIK BANGUNAN SMK NEGERI 5 PADANG - 2059-2062, Daiki Agustio Nilma (CIVED, 2018)
Abstract—This research is motivated by the low score of students on the subjects of engineering drawing. So this study aims to reveal the influence of the learning environment on student learning outcomes on the subjects Figure Technical Engineering Student Class X TGB Department of Building Engineering SMK Negeri 5 Padang academic year 2016/2017. This research is a quantitative research with correlational approach. To know the validity of questionnaire learning environment writer using Microsoft Excel program with criteria rhitung ≥ rtabel then the item is declared valid and obtained statement that fall as many as 12 item. The population of this study amounted to 64 students of the academic year 2016/2017. The sample of the research was 50 students because the research was conducted in the academic year 2017/2018, using Total Sampling technique. The result of research is got big correlation value from r table 0,279 that is equal to 0,852, significant value t test 11,292>ttabel 1,67722. Thus the hypothesis in this study is there is a significant influence between the learning environment on student learning outcomes class X TGB on the Manual Figure Drawing Engineering Engineering Department Building SMK Negeri 5 Padang. Keywords:Learning Environment, Learning Outcomes.